2010
DOI: 10.1111/j.1472-765x.2010.02937.x
|View full text |Cite
|
Sign up to set email alerts
|

rRNA-based analysis to monitor succession of faecal bacterial communities in Holstein calves

Abstract: Aims:  To quantitatively analyse the faecal bacterial communities of Holstein calves and track their succession up to 12 weeks of age. Methods and Results:  Faecal samples obtained from four female Holstein calves were analysed by the RNA‐based, sequence‐specific rRNA cleavage method. Twelve scissor probes covering major rumen bacterial groups were used, detecting c. 60–90% of the total 16S rRNAs. At 1 week of age, 16S rRNAs from members of the Bacteroides‐Prevotella group (40·0% of the total 16S rRNAs), Faeca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
95
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 49 publications
17
95
2
2
Order By: Relevance
“…The high proportion of assigned genus information observed in the large-intestinal communities may be due to their resemblance to the fecal bacterial community, which has been studied more extensively than the small intestine community. Uyeno and colleagues reported that the fecal microbiomes of 3-week-old dairy calves consist of 39.2% BacteroidesPrevotella group, 17.7% Clostridium coccoides-Eubacterium rectale group, and 11% Faecalibacterium (8). Colon samples from the 3-week-old calves used in the present study revealed similar levels for the Bacteroides-Prevotella group (32.5%) and Faecalibacterium (12.1%).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The high proportion of assigned genus information observed in the large-intestinal communities may be due to their resemblance to the fecal bacterial community, which has been studied more extensively than the small intestine community. Uyeno and colleagues reported that the fecal microbiomes of 3-week-old dairy calves consist of 39.2% BacteroidesPrevotella group, 17.7% Clostridium coccoides-Eubacterium rectale group, and 11% Faecalibacterium (8). Colon samples from the 3-week-old calves used in the present study revealed similar levels for the Bacteroides-Prevotella group (32.5%) and Faecalibacterium (12.1%).…”
Section: Discussionsupporting
confidence: 62%
“…The fecal bacterial composition of dairy calves undergoes dynamic changes during the first 12 weeks of life (8). These changes include the appearance of new species such as Ruminococcus flavefaciens and Fibrobacter species and the disappearance of Bifidobacterium, Enterobacteriaceae, Streptococcus, and Lactobacillus species (8), suggesting that both diet and gut development may drive changes in the bacterial composition during early life.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural methods used in this work are useful for the quantification of specific populations. To determine a change in any of the predominant populations in the complex intestinal microbiota is suggested to use rRNA-based analysis (Mayer et al 2012, Uyeno et al 2010.…”
Section: Resultsmentioning
confidence: 99%
“…The prokaryotic cells in 1 ml of 152 the suspensions were disrupted by glass bead beating (Uyeno et al, 2010a), and the total 153 RNAs were extracted with 1 ml of phenol equilibrated with a buffer consisting of 10 154 mmol/l EDTA, 50 mmol/l sodium acetate (pH 5.1). Aliquots of 0.5 ml of the aqueous 155 phase were obtained by centrifugation for 5 min at 12000  g at 4°C, followed by 156 purification using an RNeasy mini kit (Qiagen, calculation to determine the 16S rRNA population of the target group in total 16S 166 rRNAs were performed as described previously (Uyeno et al, 2007).…”
Section: Sampling Rna Extraction and Quantification Of Fecal Microbmentioning
confidence: 99%